'Let them entertain themselves': the fall of the Mubarak regime seen through Egyptian political cartoons. Issue 3 (4th May 2018) - Saleh, Rania
ABSTRACT: This article examines the issues underlying the downfall of the Mubarak regime from the perspective of Egyptian cartoonists. A total of 2734 political cartoons published in five leading newspapers between January 2010 and February 2011 are analyzed. Because they form a significant part of the cultural context within which these cartoons are created, popular political jokes are also referenced. The study identifies political stagnation, domestic issues and corruption as the three most significant issues that paved the road to the fall of Mubarak.